Low Bottleneck Detection in Long-Lived Species Despite Lost Genetic Diversity: A Case Study of Tuatara and Eastern Massasauga Rattlesnakes. (27th April 2021) - Bradke, Danielle R; Altobelli, Joseph T; Russell, Amy L; Jaeger, Collin P; Moore, Jennifer A
Abstract: Population bottlenecks can reduce genetic diversity and may lead to inbreeding depression. However, some studies have provided evidence that long lifespans buffer negative genetic effects of bottlenecks. Others have cautioned that longevity might merely mask the effects of genetic drift, which will still affect long-term population viability. We used microsatellite data from actual populations of tuatara ( Sphenodon punctatus ) and eastern massasaugas ( Sistrurus catenatus ) as a starting point for simulated population declines to evaluate the performance of bottleneck tests under a range of scenarios. We quantified losses in genetic diversity for each scenario and assessed the power of commonly used tests (i.e., M-ratio, heterozygosity excess, and mode-shift) to detect known bottlenecks in these moderate- to long-lived species. Declines in genetic diversity were greater in bottlenecks simulated for eastern massasaugas, the shorter-lived species, and mode-shift and heterozygosity excess tests were more sensitive to population declines in this species. Conversely, M-ratio tests were more sensitive to bottlenecks simulated in tuatara. Despite dramatic simulated population declines, heterozygosity excess and mode-shift tests often failed to detect bottlenecks in both species, even when large losses in genetic diversity had occurred (both allelic diversity and heterozygosity). While not eliminating type II error, M-ratio tests generally performed best and were most reliable when a critical value ( M c ) of 0.68 was used. However, in tuatara simulations, M-ratio tests had high rates of type I error when M c was calculated assuming θ = 10. Our results suggest that reliance on these tests could lead to misguided species management decisions.